revisión gareth matthews, the child’s philosopher, maughan rollins gregory & megan jane laverty, eds. london & new york: routledge, 2022 - kennedy, david k (2021)
This book may be described as a Festschrift—or more accurately a Gedenkschrift, given that it is a posthumous celebration of Gareth Matthews’ (1929-2011) work and career. It consists of a selected anthology of his papers, interspersed with papers by scholars that offer interpretive  perspectives on his work . The Matthews papers, which are brilliantly chosen, represent only one dimension of his oeuvre; he was in fact a recognized scholar of ancient and medieval philosophy, particularly Plato, Aristotle and Augustine. The present selection draws from his persistent, oddly related inquiry, pursued over the course of almost 40 years, into the theory and practice of conducting philosophical conversations with children, whether inside or outside the classroom.